A COMPARATIVE ANALYSIS OF GENDERED LANGUAGE FEATURES: THE MALE AND FEMALE PROTAGONISTS IN FRUITS BASKET - Syuhra, Marsha Aqillah Putri (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
This study presents a comparative analysis of gendered language features as exhibited by the male and female protagonists in the anime series Fruits Basket (Season 1). Grounded in Deborah Tannen’s (1990) sociolinguistic framework, which posits that male and female communication styles often reflect contrasting cultures, a “report talk” prioritizing status and independence versus a "rapport talk" emphasizing connection and intimacy. This research examines the dialogue of Souma Kyo and Honda Tohru. Employing a qualitative descriptive methodology, the study conducted a close textual analysis of the series' transcripts to identify and categorize distinctive linguistic patterns. The findings indicate a pronounced divergence in their communicative strategies. Kyo’s language is characterized by directness, imperative commands, and confrontational rhetoric, aligning with Tannen’s concept of a report talk oriented towards asserting dominance and achieving conversational goals. Conversely, Tohru consistently employs linguistic features designed to build rapport, including frequent use of polite forms, mitigating devices, and empathetic expressions, demonstrating a primary concern for her interlocutor's emotional state and the maintenance of harmonious relationships. These results not only corroborate Tannen’s theoretical distinctions within a popular media text but also illustrate how fictional narratives can mirror and reinforce broader sociolinguistic patterns. It is recommended that future research explores these dynamics across different cultural contexts and narrative genres to further validate these observations.